On a class of singular hyperbolic equation with a weighted integral condition - Said Mesloub; Abdelfatah Bouziani (International Journal of Mathematics and Mathematical Sciences)
In this paper, we study a mixed problem with a nonlocal condition for a class of second order singular hyperbolic equations. We prove the existence and uniqueness of a strong solution. The proof is based on a priori estimate and on the density of the range of the operator generated by the studied problem.